How to Talk to Data Scientists : A Guide for Executives. - Elser, Jeremy. (Studien Zum Physik- und Chemielernen Series, 2021)
This book provides business executives with a concrete exercise, populating a "Master Table," accessible to nontechnical managers and data scientists, which serves as the connective tissue between them. Rather than teach a diluted version of data science, this book describes how to start projects and how to detect and fix problems--the moments when leadership is critical. Insights are provided through real world examples, including a Playbook featuring common projects. The intended audience is executives (C-suite through VP). However, ambitious mid-level managers and data scientists will also benefit.